Pemanfaatan Limbah Plastik untuk Ecobrick sebagai Solusi Peningkatan Kesadaran Pengelolaan Sampah di Kelurahan Balun - Rohmad Apriyanto; Eko Arief Cahyono; Kholishatul Lailiyah; M Rizqi Romadloni; Rizqi Ramadhani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Plastic waste is an urgent environmental problem, especially in Balun Village. Inappropriate management can cause serious pollution. To increase public awareness about waste management, activities were held to utilize plastic waste to make ecobricks. Ecobricks is a technique of compacting plastic waste into plastic bottles, producing materials that can be used as building materials or functional items. This activity involves educating and training the public about the negative impacts of plastic waste, the concept of ecobricks, and practical steps for making them. The participatory approach invites people to actively manage their household plastic waste into useful ecobricks. In addition, this activity aims to build collective awareness about the importance of protecting the environment and promoting a sustainable lifestyle. The expected results are changes in community behavior in managing plastic waste, creating useful ecobrick products, and initiating a community-based environmental movement in Balun Village. In this way, this program provides a solution to the plastic waste problem and contributes to strengthening community solidarity and innovation in maintaining environmental sustainability.